2014
DOI: 10.1111/weng.12051
|View full text |Cite
|
Sign up to set email alerts
|

Language revolution behind the cultural curtain

Abstract: This paper focuses on the innovative, revolutionary features of the World Englishes paradigm that shook the education world in the late 20th century. I speak about key concepts that are salient to the paradigm, such as pluricentricity, diversity, functionality, and equality as articulated by Kachru, such as inclusivity and variability, as well as the controversies emerging in and related to education, for example, the struggle between prescriptive and descriptive approaches, and norms and usage. With reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The WE paradigm, which emerged in the 1960s (Kachru 1961, Beliayeva & Potapova 1961 and has developed since, with its theoretical basis brought into focus especially in the 1980-1990s (Kachru 1986, Kachru & Smith 1985, Smith 1987, Smith & Forman 1997, see also Bolton 2020), is a revolutionary theory (Proshina 2014a), as it has radically challenged the traditional views on the Empire's linguistic dominance, flipped sociolinguistic ideas, and drastically changed pedagogical beliefs that had found their way into English language teaching and learning. To summarize the major premises, the following arguments should be highlighted:…”
Section: The We Paradigm and How It Differs From Other Theoriesmentioning
confidence: 99%
“…The WE paradigm, which emerged in the 1960s (Kachru 1961, Beliayeva & Potapova 1961 and has developed since, with its theoretical basis brought into focus especially in the 1980-1990s (Kachru 1986, Kachru & Smith 1985, Smith 1987, Smith & Forman 1997, see also Bolton 2020), is a revolutionary theory (Proshina 2014a), as it has radically challenged the traditional views on the Empire's linguistic dominance, flipped sociolinguistic ideas, and drastically changed pedagogical beliefs that had found their way into English language teaching and learning. To summarize the major premises, the following arguments should be highlighted:…”
Section: The We Paradigm and How It Differs From Other Theoriesmentioning
confidence: 99%
“…To unpack the cultural category of Chinese zodiac animals, people need to be aware of the applied cultural linguistics framework of cultural schemas and metaphors, and world Englishes practices in relation to lexical borrowing and semantic variation. People should also take interdisciplinary perspectives to enhance the ‘intelligibility of form, comprehensibility of meaning, and interpretability of sense’ (Proshina, , p. 4) while communicating in world Englishes.…”
Section: Discussionmentioning
confidence: 99%
“…World Englishes, as a discipline and paradigm, is ‘inclusive of all varieties and variants of English, of many cultures and ethnicities, of many topics and subjects, of various approaches and perspectives’ (Proshina, , p. 2). In this case, different cultural categories, schemas and metaphors also contribute essentially to the ‘inclusivity’ of world Englishes, although they may involve ‘communicational risks’ (Davis, , p. 26) among speakers of world Englishes.…”
Section: Discussionmentioning
confidence: 99%
“…The World Englishes (WE) paradigm (e.g. Bolton 2020, Kachru and Smith 1985, Proshina 2014, Proshina and Nelson 2020, Smith and Forman 1997, "has radically challenged the traditional views on the Empire's linguistic dominance, flipped sociolinguistic ideas, and drastically changed pedagogical beliefs that had found their way into English language teaching and learning" (Proshina and Nelson 2020: 526) including teaching translation. It has convincingly showed that English is not a monolithic and homogeneous language anymore; being pluricentric, it has differentiated into a great number of varietiesworld Englishes (cf.…”
Section: Introductionmentioning
confidence: 99%